2001
DOI: 10.1007/s004970100090
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization and expression of transgenes in gametes and zygotes

Abstract: The in vitro fertilization system of maize is the well characterized model system for the fertilization process and early zygotic embryogenesis of higher plants. Application of molecular methods to the in vitro fertilization system led to the isolation of new genes and uncovered specific expression patterns of cell cycle regulators. Recent studies showed that expression of transgenes is possible in gametes and zygotes, thus transgenic approaches might offer an opportunity to unravel the roles of genes during f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Obtaining distant hybrids and genetically modified artificial zygotes has been a frequently cited goal of in vitro fertilization, so it is interesting that transgenes in gametes and in in vitro-fertilized zygotes have now been achieved (Scholten and Kranz, 2001). The use of promoters specific to the germline (e.g., the promoter of the generative cell-specific gene lilium generative cell 1 (LGC1), which is activated in the generative and sperm cells [Singh et al, 2003]) could alter gene expression in the germline to achieve novel expression in seeds or in the next generation.…”
Section: In Vitro Studies Of Fertilization In Flowering Plantsmentioning
confidence: 99%
“…Obtaining distant hybrids and genetically modified artificial zygotes has been a frequently cited goal of in vitro fertilization, so it is interesting that transgenes in gametes and in in vitro-fertilized zygotes have now been achieved (Scholten and Kranz, 2001). The use of promoters specific to the germline (e.g., the promoter of the generative cell-specific gene lilium generative cell 1 (LGC1), which is activated in the generative and sperm cells [Singh et al, 2003]) could alter gene expression in the germline to achieve novel expression in seeds or in the next generation.…”
Section: In Vitro Studies Of Fertilization In Flowering Plantsmentioning
confidence: 99%
“…Although the success has so far been confi ned in achieving fertilization and embryo development between gametes of compatible species, studies of Kranz and his associates (Kranz 1997(Kranz , 2008Scholten and Kranz 2001 ) have shown that there is no technical diffi culty in achieving in vitro fertilization between isolated egg and sperm cells in interspecifi c and intergeneric combinations. However, the development of zygotes is restricted to crosses between closely related species (Kranz and Dresselhaus 1996 ).…”
Section: In Vitro Fertilizationmentioning
confidence: 99%
“…This goal may not be distant, as Scholten & Kranz (2001) have now demonstrated the expression of transgenes in gametes and in vitro fertilized zygotes. With the use of germ-linespecific promoters (for instance, the LCG1 promoter; Xu et al 1999b), alterations could be rapidly incorporated in the germ line for transmission or reimplantation in host plants to produce seed.…”
Section: Adhesion and Characteristics Of In Vitro Fusionmentioning
confidence: 99%